Methodologies for Patellid Limpets’ Aquaculture: From Broodstock Management to Juveniles - Castejón, Diego; García, Loreto; Cañizares, José M.; De Girolamo, Mirko; Nunes, Carla; Isidro, Eduardo; Courtois de Viçose, Gercende; Nogueira, Natacha; Andrade, Carlos A. P. (Frontiers in Marine Science, 2022)
The production of cultured limpets is a recent research field contributing to aquaculture diversification, focusing on low trophic species while reducing the carbon footprint. Limpets are gastropods that colonize rocky substrates and are mostly present on tidal and subtidal shores. This animal group is in high commercial demand and is endangered in several regions. The aquaculture production of limpets has been traditionally challenging. The most successful reproduction method has been gonadal dissection, as artificial spawning induction has shown limited success to date. Moreover, methods for larval culture, settlement, and juvenile growth have been poorly developed and remain largely unknown. In recent years, advances in this field have led to the optimization of methods to enhance larval production, larval culture, settlement induction of competent larvae, and management of post-larvae and juveniles. The present manuscript reviews these advances, obtained within the framework of AQUAINVERT project, focusing on broodstock management, gametes release, larval production, larviculture, settlement, and grow-out of post-larvae, and providing an update on the actual state of the art in limpets’ aquaculture.